2016
DOI: 10.1590/s1984-29612016086
|View full text |Cite
|
Sign up to set email alerts
|

Hematological changes associated with hemoplasma infection in cats in Rio de Janeiro, Brazil

Abstract: This study aimed to detect Mycoplasma spp. in naturally infected cats from Rio de Janeiro and to evaluate hematological abnormalities and factors associated with this infection. Out of the 197 cats sampled, 11.2% presented structures compatible with hemoplasma organisms on blood smears. In contrast, 22.8% were positive for Mycoplasma spp. by means of 16S rRNA gene real-time polymerase chain reaction, which reflects the weak concordance between techniques. The infection rates, by means of 16S rRNA gene conventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
(58 reference statements)
5
12
0
Order By: Relevance
“…Thrombocytopenia (86%) and anaemia (40%) were the most common haematological signs in the current study. Our results are in line with the results of Raimundo et al (2016), who determined the most common hematological findings as anaemia and thrombocytopenia. Thrombocytopenia may be due to the destruction and consumption of platelets, increased hepatic or splenic platelet sequestration, decreased platelet production following bone marrow hypoplasia, and production of antiplatelet antibodies.…”
Section: Discussionsupporting
confidence: 92%
“…Thrombocytopenia (86%) and anaemia (40%) were the most common haematological signs in the current study. Our results are in line with the results of Raimundo et al (2016), who determined the most common hematological findings as anaemia and thrombocytopenia. Thrombocytopenia may be due to the destruction and consumption of platelets, increased hepatic or splenic platelet sequestration, decreased platelet production following bone marrow hypoplasia, and production of antiplatelet antibodies.…”
Section: Discussionsupporting
confidence: 92%
“…M. turicensis’ or ‘ Ca . M. haemominutum’ alone 41 . Macroscopic examination of one pig in the present case revealed similar results as observed after infection with M suis (icterus, ascites, liver alterations, pale mucus membranes) 42 .…”
Section: Discussionsupporting
confidence: 85%
“…Co-positivity for the different species of hemoplasma has been described in felines, mainly among the most prevalent species in the region, and tends to prevail in male felines (SANTOS et al, 2014;DUARTE et al, 2015), as also found in this study. Male felines may be at increased risk for hemoplasma infection due to frequent fights over territory disputes and females in estrus (JENKINS et al, 2013;RAIMUNDO et al, 2016). Although the association of Mhm infection with anemia has already been described in other studies (SANTOS et al, 2014), in this study no association with anemia was observed by any of the investigated agents, although the feline population came from a veterinary hospital similar to the studies of Aquino et al (2014), Spada et al (2014), andVergara et al (2016).…”
Section: Introductionsupporting
confidence: 55%